Comparative study of myocardial function in cases of feline hypertrophic cardiomyopathy with and without dynamic left-ventricular outflow-tract obstruction - Saito, Takahiro; Suzuki, Ryohei; Yuchi, Yunosuke; Fukuoka, Haru; Satomi, Shuji; Teshima, Takahiro; Matsumoto, Hirotaka (Frontiers in Veterinary Science, 2023)
In recent years, hypertrophic cardiomyopathy (HCM) in cats has become much more common in clinical practice due to improvements in diagnostic techniques and equipment performance. One phenotype is obstructive HCM with left ventricular (LV) outflow tract obstruction (DLVOTO). It has been reported that the presence or absence of DLVOTO does not affect long-term prognosis in cats with HCM. In this study, we evaluated and compared myocardial function in HCM-affected cats with and without DLVOTO using the two-dimensional speckle-tracking echocardiography. LV longitudinal strain of the endocardial, epicardial, and whole layer and LV circumferential strain of the epicardium were significantly decreased in all HCM-affected cats compared to healthy cats. However, these values were not significantly different between those with and without DLVOTO. In contrast, the endocardial and whole layers of LV circumferential strain were only significantly decreased in HCM-affected cats with DLVOTO compared to healthy cats. This could be attributed to the fact that the LV pressure load associated with DLVOTO affected the endocardial myocardium more in the LV endocardial layer, and that lower values of LV endocardial strain lowered the values of LV strain in the whole layer. In conclusion, our results suggest that LV myocardial function may have been more compromised in the HCM-affected cats with DLVOTO.